İhracat teşvikleri kapsamında dahilde işleme izninin yeri ve önemi - Şensoy, Mehmet (My University, 2006)
During the negotiations that were held in the frame of Eu and the Customs Union Agreement, among organizations such as GATT (General Agreement on Tariffs and Trade) and WTO (World trade Organization), subjects such as the annulment of national aids under the form of cash payments and export promotions that are not monetary aids, were included in the order of the day. Nowadays exports promotions are principally made under the following forms: Custom Exemptions in Sales and Deliveries considered as exports, Exemption of Duty Taxe, Export Credit and Insurance Program, VAT Exemption in Export, National Assistance to Export and Inward Processing Procedure. With its 50% part in the whole of our exports, the Inward Processing Procedure has the most important place among export promotions. The Inward Processing Procedure, is a procedure where, by linking to a caution the taxes of objects that are not included in free circulation or by proceeding in the Customs Territory of Turkey objects included in free circulation or having the same value, where the export of objects that have already been submitted to a processing is basic, in case the export is realized, the caution or tax that has been collected is returned. The Inward Processing Procedure not only represents a facility for realizing an import entry through world market prices (raw materials, semi finished and finished products) but it also creates a liquidity as taxes are not being paid during import and are connected to a caution and as it is not linked to imported entries trade policy measures, it prevents any loss of time and additional financial burdens.
Keywords: İhracat_İşleme İzni